2019
DOI: 10.1016/j.jcf.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Growth failure and treatment in cystic fibrosis

Abstract: Poor growth has long been a characteristic feature of cystic fibrosis (CF) and is significantly linked to lung function and overall health status. Improvements in pulmonary and nutrition care for patients with cystic fibrosis (CF) have resulted in better growth outcomes; however, height gains have not paralleled the improvements in weight in children with CF, and patients with more severe CF mutations remain significantly more affected. Many factors affect the growth hormone-IGF-1 axis and the growth plate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 77 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…However, the data are inconsistent, and use of growth hormone should only be considered on a case by case basis. Further discussion of growth hormone is covered in article 11, section 4, Growth Failure and Treatment in CF, [50].…”
Section: Complications and Their Managementmentioning
confidence: 99%
“…However, the data are inconsistent, and use of growth hormone should only be considered on a case by case basis. Further discussion of growth hormone is covered in article 11, section 4, Growth Failure and Treatment in CF, [50].…”
Section: Complications and Their Managementmentioning
confidence: 99%
“…The different mechanisms involving cAMP, PLC/PKC, NO/cGMP, and PKA, contribute to modulate Ca 2+ influx and the secretion of GH in vertebrates including fish. The secretion of GH in both fish and mammals follows a pulsatile, circadian pattern, with relatively higher release during the dark phase ( 7 , 13 , 14 , 28 , 38 ). Besides, sexual dimorphism in GH secretion was observed in rats ( 66 ) and humans ( 67 , 68 ), with large nocturnal GH pulses and low inter–peak levels in males, and a higher interpeak and more sustained secretion in females ( 38 ).…”
Section: Gh Secretionmentioning
confidence: 99%
“…Moreover, recombinant human IGF-1 replacement has been useful in reversing the adverse conditions associated with GH deficiency or GH insensitivity in children ( 10 , 11 ). GH treatment was also found useful in treating some catabolic conditions such as AIDS wasting and cystic fibrosis ( 2 , 9 , 12 , 13 ). In addition to its clinical relevance as a key molecule of the GH/IGF axis ( Figure 1 ), GH is a pleiotropic hormone involved in several vital processes in vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…Results of studies evaluating the GH/IGF-1 axis in patients with CF confirm relative resistance to GH, but data concerning the pattern of GH secretion are scarce [9,68,[91][92][93]. Ciro et al [91] reported both GH insufficiency and reduced IGF-1 levels in CF children.…”
Section: The Effects Of Childhood-onset Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…A number of studies, both experimental and clinical, were conducted to better explain the impact of chronic inflammation on postnatal growth and pubertal development during childhood. It has been confirmed that the effects of pro-inflammatory cytokines, such as interleukin 6 (IL-6), tumour necrosis factor-α (TNF-α), and interleukin 1β (IL-1β), are some of the most significant factors, besides malnutrition, chronic stress, and prolonged use of glucocorticoids, which impair the activity of the GH/IGF-1 axis, and consequently lead to growth retardation in children suffering from childhood-onset chronic inflammatory diseases [8,10,23,[31][32][33][34][35][36][37][38]. In everyday clinical practice, the most common chronic inflammatory diseases associated with growth impairment are inflammatory bowel disease (IBD) -especially Crohn's disease, cystic fibrosis (CF), and juvenile idiopathic arthritis (JIA) [8,9,28,39,40].…”
Section: Introductionmentioning
confidence: 99%